Review of Legal Protection Against Auction Winners in Good Faith Against Auctions of Lien Assets Sued by Debtors - Merlin Soman (SEAN Institute, 2025)
In practice, auction winners often face legal risks, including lawsuits from debtors claiming rights to the auction object despite having followed legal auction procedures. This study aims to analyze the legal protection for auction winners in good faith for dependent rights assets sued by debtors, considering that auctions as a solution to bad loans often cause legal problems related to the rights of debtors and creditors. The research method is normative juridical with an approach to legal rules, conceptualization, and cases, using data from regulations, court decisions, and legal literature. The results of the study show that legal protection for auction winners in good faith is regulated in the Law on Dependent Rights, Regulation of the Minister of Finance, and jurisprudence, but its implementation is limited by proof of good faith and coordination between institutions. Debtor lawsuits can hinder the preservation of rights and create convenience. In conclusion, legal protection needs to be strengthened through the socialization of auction regulations, increasing the professionalism of auction implementation, harmonization of regulations, and effective dispute resolution mechanisms to reduce the impact of debtors' lawsuits on the legal certainty of auction winners.